Nausea and vomiting of pregnancy - studies with pregnancy-unique quantification of emesis questionnaire - Laitinen, Linda (fi=Turun yliopisto|en=University of Turku|, 2023)
Majority of women experience at least some degree of nausea and vomiting of pregnancy (NVP). The severity of the condition ranges from mild symptoms to intractable nausea and vomiting, hyperemesis gravidarum (HG). An internationally widely used questionnaire, the Pregnancy-Unique Quantification of emesis (PUQE), has been developed to categorise the severity of NVP. The present study aimed to assess the usability of the PUQE both in inpatient and outpatient settings for the first time in Finland. Moreover, associations between NVP and maternal factors, physical quality of life (QoL), mental QoL and sleep quality were assessed. The PUQE was applied in two cohorts of pregnant women: 106 hospitalised women with HG and 2411 women recruited from maternal health care clinics (MHCC). At the hospital, among women with HG, the PUQE scores decreased from admission to discharge, reflecting the alleviation of HG. The change in PUQE scores was associated with improved physical QoL and in repeated admissions also with improved mental QoL. The women recruited from MHCCs recalled the worst NVP in their current pregnancy and replied to the PUQE accordingly. In general, NVP was frequent and most often rated as moderate. The severity of NVP was mainly associated with higher gravidity and previous nausea related to motion sickness, migraine, and other kind of headache. In addition, family history of NVP was associated with more severe NVP. Further, women with more severe NVP had worse physical QoL, worse mental QoL and worse sleep quality. Moreover, the women replied the PUQE at different gestational weeks, but the PUQE total scores were comparable whether the scores were given in early or in late pregnancy. The findings of the present study support clinical use of the PUQE also in Finland. The PUQE scores were usable at hospital in HG treatment follow-up. In outpatient care the PUQE could be used as a screening tool to assess the severity of NVP. Using the PUQE for the severity assessment of NVP, the present study found various associative factors for NVP. Notably, along increasing severity of NVP the present study highlighted the deterioration of QoL and sleep quality. These results are important in antenatal counselling.

Raskauspahoinvointi – Tutkimuksia Pregnancy-Unique Quantification of Emesis -kyselykaavakkeella Suurin osa odottajista kokee jonkinasteista raskauspahoinvointia, jonka vaikeusaste vaihtelee lievästä aina hallitsemattomaan pahoinvointiin ja oksenteluun nimeltään hyperemesis gravidarum (HG). Raskauspahoinvoinnin vaikeusasteen luokitteluun on kehitetty kansainvälisesti laajasti käytetty kyselykaavake Pregnancy-Unique Quantification of Emesis (PUQE). Tässä väitöstutkimuksessa selvitettiin PUQEn käytettävyyttä sekä sairaalassa että avoterveydenhuollossa ensimmäistä kertaa Suomessa. Lisäksi tutkittiin äidin ominaisuuksien, fyysisen ja psyykkisen elämänlaadun sekä unen laadun yhteyttä raskauspahoinvointiin. PUQEa käytettiin kahdessa eri raskaana olevien aineistossa: 106 naisella, jotka olivat HG:n vuoksi sairaalahoidossa ja 2411 neuvoloista rekrytoiduilla odottajilla. Sairaalassa PUQE-pisteet laskivat tulopäivästä lähtöpäivään kuvastaen HG:n lieventymistä. Tämä muutos oli yhteydessä kohentuneeseen fyysiseen elämänlaatuun ja toistuvissa hoitojaksoissa myös kohentuneeseen psyykkiseen elämänlaatuun. Neuvoloista rekrytoidut odottajat vastasivat PUQEn raskauden pahimman pahoinvointijakson mukaisesti. Raskauspahoinvointi oli yleistä ja PUQEn mukaan yleisimmin keskivaikeaa. Aiemmat raskaudet, matkapahoinvointitausta ja taipumus pahoinvointiin migreenin tai muun päänsäryn yhteydessä sekä sukulaisilla esiintynyt raskauspahoinvointi olivat yhteydessä voimakkaampaan raskauspahoinvointiin. Niillä naisilla, joilla raskauspahoinvointi oli voimakkaampaa, oli myös sekä huonompi fyysinen ja psyykkinen elämänlaatu että huonompi unen laatu. Odottajat vastasivat PUQEn eri raskausviikoilla, mutta PUQE-pisteet olivat vertailukelpoisia alkuraskauden ja loppuraskauden vastausten välillä. Väitöstutkimuksen mukaan PUQE sopii hyvin kliiniseen käyttöön myös Suomessa. PUQE soveltuu sairaalahoidossa HG potilaiden hoitovasteen seurantaan. Avoterveydenhuollossa PUQE soveltuu raskauspahoinvoinnin voimakkuuden seulontaan. Väitöstutkimus toi esiin useita raskauspahoinvoinnin taustatekijöitä sekä sen elämänlaatua ja unen laatua heikentävän vaikutuksen. Tuloksia voidaan hyödyntää odottajien neuvonnassa.